Impaired Color Discrimination in Alzheimer Disease Dementia. (1st January 2022) - Boedeker, Sebastian; Halstenberg, Eileen; Schulz, Philipp; Beblo, Thomas; Kreisel, Stefan; Driessen, Martin; Toepper, Max
Abstract : Objective: Patients with Alzheimer disease dementia (ADD) often show impaired orientation and navigation. Signage offers an opportunity to compensate for these deficits, communicate information efficiently and facilitate wayfinding. Certain properties of signs such as colors and contrasts may beneficially affect the uptake and processing of information particularly in ADD patients. Methods: Thirty-six healthy older adults and 30 ADD patients performed a computerized color perception task that required discriminating different color combinations. The effects of different contrast features on performance accuracy and speed in the 2 experimental groups were examined by nonparametric mixed analysis of variances. Results: Analyses revealed a significant effect of contrast polarity on reaction times, significant effects of group on reaction times and errors as well as a marginally significant interaction of group×color on errors. All participants benefitted from positive contrast polarity (ie, dark target on lighter background) as indicated by increased performance speed. Furthermore, ADD patients reacted slower and less accurate than healthy controls, but showed higher accuracy at black-white and red-yellow than at blue-green color combinations. Conclusions: Our findings suggest the implementation of signs with positive contrast polarity to ensure faster reactions. In addition, certain color combinations may enhance accuracy, particularly in patients with ADD.